Toward Free and Fair Trade: A Global Public Good Perspective - Mendoza, Ronald U (Archīum Ateneo, 2002)
The world's rich nations have long preached the advantage of free trade for the world's developing nations. But it simply has not been a level playing field. This in-depth piece shows how and why. The authors argue that the free trade regime is often rigged against the developing nations, and they propose mechanisms to make trade not merely freer but fairer.